Molecular Dynamics, Phase Transition and Frequency‐Tuned Dielectric Switch of an Ionic Co‐Crystal - Liu, Jing‐Yan; Zhang, Shi‐Yong; Zeng, Ying; Shu, Xia; Du, Zi‐Yi; He, Chun‐Ting; Zhang, Wei‐Xiong; Chen, Xiao‐Ming (Angewandte Chemie International Edition, 2018)
Dielectric switches that can be converted between high and low dielectric states by thermal stimuli have attracted much interest owing to their many potential applications. Currently one main drawback for practical application lies in the non‐tunability of their switch temperatures (TS). We report here an ionic co‐crystal (Me3NH)4[Ni(NCS)6] that contains a multiply rotatable Me3NH+ ion and a solely rotatable one due to a more spacious supramolecular cage for the former one. This compound undergoes an isostructural order–disorder phase transition and it can function as a frequency‐tuned dielectric switch with highly adjustable TS, which is further revealed by the variable‐temperature structure analyses and molecular dynamics simulations. In addition, the distinct arrangements and molecular dynamics of two coexisting Me3NH+ ions confined in different lattice spaces as well as the notable offset effect on the promoting/hindering of dipolar reorientation after dielectric transition provide a rarely observed but fairly good model for understanding and modulating the dipole motion in crystalline environment. Dipole motion in a crystal: The ionic co‐crystal (Me3NH)4[Ni(NCS)6] undergoes an order–disorder phase transition and functions as a frequency‐tuned dielectric switch with a highly adjustable switching temperature. The distinct arrangements and molecular dynamics of two coexisting Me3NH+ ions provide a model for understanding/modulating the dipole motion in a crystalline environment.